Providing a new route for chemical recycling of plastics by aspen plus simulation, energy, and its carbon dioxide emissions analysis - Ali Nazari; Mohsen Salimi; Majid Amidpour; Ali Behbahani-Nia (Results in Engineering)
In this research, a new complex is proposed for chemical recycling of plastic. After determining the plastic waste entering this process, the sections in which chemical reactions occur have been simulated through aspen plus, such as: gasification of plastic waste and purifying, methanol production, methanol decomposition to various chemicals such as ethylene, propylene, and methane, separation processes for these products, methane decomposition to benzene and the separation of the products of this part, single-step production of styrene from benzene and ethylene, and the polymerization processes. Furthermore, the impacts of this complex on issues such as plastic recycling, energy consumption, and carbon dioxide emissions are studied and compared to conventional methods of plastic production. Results indicate that plastic waste recycling will be >98 % in the proposed model. Energy consumption is decreased by 29 %, carbon dioxide in this part is decreased by 53 % by using renewable energy for its power consumption. These results show the sustainability, and circularity of the proposed model.